The impact of obesity on cardiovascular structure and function: the fetal programming era - St-Pierre J; Bouchard L; Poirier P (Dove Medical Press, 2012)
Julie St-Pierre1, Luigi Bouchard2,3, Paul Poirier41Department of Pediatrics, Chicoutimi Hospital, Saguenay, QC, Canada; 2Department of Biochemistry, Université de Sherbrooke, Sherbrooke, QC, Canada; 3ECOGENE-21 and Lipid Clinic, Chicoutimi Hospital, Saguenay, QC, Canada; 4Quebec Heart and Lungs Institute, Université Laval, Quebec, QC, CanadaAbstract: The burden of obesity is now well established as a precursor of cardiovascular disease and other disorders. Although better clinical guidelines exist to prevent and treat obesity, the prevalence of obesity among children and adolescents is increasing alarmingly. Primary prevention remains the gold standard to significantly reduce the public health concerns associated with obesity. Traditional cardiovascular disease risk factors (such as dyslipidemia, hypertension, type 2 diabetes) for cardiovascular disease among children and adolescents are known. The scope of this review is thus to discuss new and emerging obesity and associated-disease risk factors. Evaluation of the coronary plaque formation, diastolic dysfunction, carotid intima-media thickness and heart rate variability represent interesting tools with clinical relevance. Beyond these new cardiovascular disease risk factors, recent evidence suggests that a detrimental fetal environment, associated with for example, maternal obesity, insulin resistance, and physical inactivity, imprints fetal metabolic programming via epigenetic mechanisms that predisposes the newborn to obesity and cardiovascular disease later in life. This information may impact on the future management of maternal health, as well as for those high-risk children.Keywords: cardiovascular disease, pediatrics, risk factors